University students and video games: Perceptions, use, and preferences according to gender - Jorge Oceja; Natalia González-Fernández (Arizona State University, 2020)
This work analyses the video game culture in terms of perceptions, use, and preferences towards video games for a group of 610 university students, focusing on the impact of gender. The study is quantitative in nature, based on a cross-sectional survey and the subsequent statistical analysis of the data. Results show that students at this stage of life play video games and that they have - to a discernible degree - a video game culture, even though differences exist between men and women. Explanations for these differences, which affect other aspects like the platforms they use and their favourite games, are explored in the final part of the article. It seems that, besides their possibilities as an emergent media, video games are cultural products permeable and embedded in a context of gender inequity. This work aims to be a starting point for designing educational projects and policies that use video games in higher education while taking advantage of the diversity that this media can offer.